2009
DOI: 10.1017/s0376892909990166
|View full text |Cite
|
Sign up to set email alerts
|

Community perceptions of four protected areas in the Northern portion of the Cerrado hotspot, Brazil

Abstract: SUMMARYEstablishing effective networks of protected areas (PAs) is one of the major goals of conservation strategies worldwide. However, the success of PAs in promoting biodiversity conservation depends on their integration to local and regional contexts, reducing and mitigating human impacts originating from buffer zones. Community perceptions affect interactions between residents and PAs, and thereby conservation effectiveness. Research at Tocantins state (northern Brazilian Cerrado), aimed to analyse local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
1
13
0
2
Order By: Relevance
“…These factors include perception about the park management and other relevant organisations (Allendorf, 2007;Gillingham and Lee, 1999;Lepp and Holland, 2006), inadequate benefits (Gillingham and Lee, 1999;Lepp and Holland, 2006), past experience with protected wildlife such as crop damage and livestock depredation (Campbell-Smith et al, 2010;Yihune et al, 2009), general conservation values (Sodhi et al, 2010), dependency on resource (Marshall et al, 2010), perceived impact of illegal resource extraction (Thapa and Chapman, 2010) and socio-economic factors related to the household and the village an individual belongs to (Anthony, 2007;Ferreira and Freire, 2009;Vodouhê et al, 2010). In the following paragraphs, we will explain how each of these factors has been found to influence attitudes and behaviour, leading to the development of a framework for modelling the likelihood of illegal resource extraction.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…These factors include perception about the park management and other relevant organisations (Allendorf, 2007;Gillingham and Lee, 1999;Lepp and Holland, 2006), inadequate benefits (Gillingham and Lee, 1999;Lepp and Holland, 2006), past experience with protected wildlife such as crop damage and livestock depredation (Campbell-Smith et al, 2010;Yihune et al, 2009), general conservation values (Sodhi et al, 2010), dependency on resource (Marshall et al, 2010), perceived impact of illegal resource extraction (Thapa and Chapman, 2010) and socio-economic factors related to the household and the village an individual belongs to (Anthony, 2007;Ferreira and Freire, 2009;Vodouhê et al, 2010). In the following paragraphs, we will explain how each of these factors has been found to influence attitudes and behaviour, leading to the development of a framework for modelling the likelihood of illegal resource extraction.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…However, respondents were confused about the park's goals, as they expected the park staff to focus on community development. Similarly, in a study in four PAs in Brazil, Ferreira and Freire (2009) found that residents were aware of the PAs' existence, but were unfamiliar with their goals.…”
mentioning
confidence: 92%
“…Conservation of large carnivores like wolves and snow leopards requires a better understanding of their conflict with humans (Namgail et al, 2007) because community perceptions and attitudes affect conservation effectiveness (Ferreira & Freire, 2009). In addition, a proper understanding of the human dimension and related social norms characterizing wildlife conflicts is essential to inform management and ensure local support (Gelcich, Edwards-Jones, Kaiser, & Castilla, 2006;Madden, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on human-carnivore conflicts in highland Asia have provided important conservation implications by understanding people's attitudes toward carnivores; either by characterizing the attitudes (Bagchi & Mishra, 2006;Ferreira & Freire, 2009;Liu et al, 2011;Oli et al, 1994;Wang, Lassoie, & Curtis, 2006) or by identifying the drivers for the attitudes (Li et al, 2015;Mishra, 1997;Suryawanshi et al, 2014). But these studies usually present surveyors' opinions as possible solutions rather than including those of local communities.…”
Section: Introductionmentioning
confidence: 99%